Towards reinforcing the waste separation at source for Vietnam's waste management: Insights from the Nudge Theory - Le Thi Thanh Loan; Raquel M. Balanay (Environmental Challenges, 2023)
Systematic review of articles published in 2018-2021 from the ScienceDirect database is done to discuss the significance of the Nudge theory for recent insights into the encouragement of waste separation at source among the households in Vietnam. The country has an institutional structure and a comprehensive legal framework and underpinnings in support to its waste management strategies for environmental protection and for the development of circular economy. In spite of this, Vietnam is beset with increasing waste problem. Synthesized information from the review supports the potential of nudges to induce waste separation at source among the households and to ensure broad social support and participation for the desired behavior. RandD is an essential process to determine the appropriate nudges that will drive the desired behavior. For Vietnam to induce waste separation at source among its households, nudge conceptualization, selection, configuration (including choice structure), administration (and conveyance), testing, and revision are critical with framing/messaging, symbolism, contextualization, association, and feedbacking, especially in structuring choices and methods of nudge implementation. Pitfalls in the use of nudges include shortfalls in the critical process of nudge configuration and administration as well as fatalistic mindsets, and non-consultative, non-inclusive and non-participatory approaches of determining the nudges. Vietnam has to pay attention to the critical considerations (including the involvement of experts) of creating nudges to be successful towards inducing waste separation at source for circular economy.